Pengaruh Edukasi Gizi Terhadap Feeding Practice Pada Ibu Dengan Balita Stunting Di Puskesmas Simpang Agung Kecamatan Seputih Agungkabupaten Lampung Tengah - Linawati Novikasari; Livia Eka Fitriana (Malahayati Nursing Journal, 2021)
ABSTRACT :   THE EFFECT OF NUTRITIONAL EDUCATION ON FEEDING PRACTICE IN MOTHER WITH STUNTING CHILDREN AT PUSKESMAS SIMPANG AGUNG KECAMATAN SEPUTIHAGUNG KABUPATEN LAMPUNGMIDDLE OF 2020 Background : Nutrition is one of the factors that determine the success of achieving optimal growth and development during toddlerhood. The golden period of growth requires proper nutritional support. Good nutrition will speed up recovery and reduce the intensity (emergency) of infectious diseases in toddlers.Purpose : Of this study was to determine the effect of nutrition education on feeding practice in mothers with stunted children at the Simpang Agung Public Health Center, Seputih Agung District, Central Lampung Regency, 2020.Method : The type of research used in this research is quantitative with the design in this study using a Quasi Experiment using the One Group Pretest Postest approach. The population in this study were all mothers who had children under five with a total of 30 mothers with a total sample of 30 mothers. In this study the sampling technique used was the total population, this is because the available population 100 respondentsResult : Based on statistical tests, it is known that the p-value is 0,000 or p-value 0.05, which means the effect of nutritional education on feeding practice in mothers with stunting children at the Simpang Agung Public Health Center, Seputih Agung District, Central Lampung Regency in 2020.Conclusion : It is known that at Simpang Agung Public Health Center, Seputih Agung District, Central Lampung Regency in 2020, the average Feeding Practice before being given nutrition education was 27.13 with a standard deviation of 8.978 and a standard error of 1.639, while after being given nutrition education the average Feeding Practice was 40.83 with a standard deviation of 10.923 and a standard error of 1.994. It is known that based on the average results before and after, the difference is 13,700. Keywords            : Nutrition Education Feeding Practice  Pendahuluan : Gizi merupakan salah satu faktor yang menentukan keberhasilan untuk mencapai tumbuh kembang optimal pada masa balita. Periode emas pertumbuhan memerlukan dukungan gizi yang tepat. Gizi yang baik akan mempercepat pemulihan dan mengurangi intensitas (kegawatan) penyakit infeksi pada balita.Tujuan : Dalam penelitian ini adalah diketahui Pengaruh Edukasi Gizi Terhadap Feeding Practice pada Ibu dengan Balita Stunting Di Puskesmas Simpang Agung Kecamatan Seputih Agung Kabupaten Lampung Tengah Tahun 2020Metode : Jenis penelitian yang digunakan dalam penelitian ini adalah kuantitatif dengan rancangan dalam penelitian ini menggunakan Quasi Eksperimen dengan menggunakan pendekatan One Group Pretes Postest. Populasi dalam penelitian ini adalah seluruh ibu yang mempunyai balita  Stunting  yang berjumlah 30 ibu dengan jumlah sampel berjumlah 30 ibu. Dalam penelitian ini teknik sampling yang digunakan adalah total populasi, hal ini dikarenakan populasi yang tersedia 100 respondenHasil : Berdasarkan uji statistic, diketahui p-value 0,000 atau p-value 0,05, yang artinya Pengaruh Edukasi Gizi Terhadap Feeding Practice pada Ibu dengan Balita Stunting Di Puskesmas Simpang Agung Kecamatan Seputih Agung Kabupaten Lampung Tengah Tahun 2020Kesimpulan : Diketahui bahwa Di Puskesmas Simpang Agung Kecamatan Seputih Agung Kabupaten Lampung Tengah Tahun 2020, rata-rata Feeding Practice sebelum diberikan edukasi gizi adalah 27,13 dengan standar deviasi 8,978 dan standar eror 1,639, sedangkan sesudah diberikan edukasi gizi rata rata Feeding Practice adalah 40,83 dengan standar deviasi 10,923 dan standar error 1,994. Diketahui berdasarkan hasil rata-rata sebelum dan sesudah, nilai selisihnya adalah 13,700. Kata Kunci               : Edukasi Gizi Feeding Practice